2020
DOI: 10.3389/fphar.2019.01635
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol Improves Lung Ischemia-Reperfusion Injury via Antiinflammation and Antioxidative Stress Regulated by SIRT1/HMGB1/NF-κB Axis

Abstract: Trauma, organ transplantation, and thromboembolism are the main causes of lung ischemia-reperfusion injury (LIRI), and new therapies and drugs are urgent to relieve LIRI. In preliminary experiment, authors found that kaempferol could improve LIRI in rats, and the current study further explored its possible mechanism. The model of rat LIRI was established and appropriate research methods were implemented. Results shown that kaempferol could significantly improve LIRI, inhibit release of inflammatory factors inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 36 publications
(36 reference statements)
2
26
0
Order By: Relevance
“…In previous studies, we have confirmed that kaempferol exerts anti-LIRI by increasing SIRT1 activity (Yang et al, 2020). In this study, we found that kaempferol can improve the stability of mitochondrial membrane potential and inhibit the opening of mPTP of L2 cells after A/R, up-regulate the levels of Bcl-2 and mitochondrial cytochrome c while downregulating the levels of Bax and cytoplasmic cytochrome c in L2 cells after A/R or lung tissue of rats after I/R.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…In previous studies, we have confirmed that kaempferol exerts anti-LIRI by increasing SIRT1 activity (Yang et al, 2020). In this study, we found that kaempferol can improve the stability of mitochondrial membrane potential and inhibit the opening of mPTP of L2 cells after A/R, up-regulate the levels of Bcl-2 and mitochondrial cytochrome c while downregulating the levels of Bax and cytoplasmic cytochrome c in L2 cells after A/R or lung tissue of rats after I/R.…”
Section: Discussionsupporting
confidence: 74%
“…The rats were randomly divided into five groups with six rats in each as follows. 1) The control group (Control), as previous ( Yang et al, 2020 ), the rats were intraperitoneally injected with 2 ml vehicle for 7 days. One hour after the last administration, rats were anesthetized with pentobarbital sodium (50 mg/kg) intraperitoneally, performed thoracotomy, exposed the trachea and then closed the chest immediately.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kaempferol ( 130 ) (3,4′,5,1-tetrahydroxyflavoune) is an aglycone flavonol which is naturally occurred in many plants’ parts through the phenylpropanoid pathway [ 102 , 103 ]. Pharmacological and biological activities of this nutraceutical compound have been extensively studied and reported to possess significant antiproliferative, cytotoxicity, anti-inflammatory, antioxidant, and antidiabetic activities [ 104 , 105 , 106 , 107 , 108 , 109 ].…”
Section: Isolation Of Various Flavonoid Classifications By Sephadementioning
confidence: 99%